Blood pressure postural changes variability is associated with cognitive decline: the S.AGES cohort. (20th December 2022) - Strumia, Mathilde; Vidal, Jean‐Sebastien; Hanon, Olivier; Rouch, Laure
Abstract: Background: Over the past decade, higher blood pressure (BP) variability has been associated with cognitive decline (CD). To date, only one study investigated the specific impact of visit‐to‐visit BP postural changes variability on dementia but its association with cognition is still unknown. We aimed to investigate the association between BP postural changes variability and cognitive function in noninstitutionalized subjects aged ≥ 65 years. Method: The S.AGES (Sujets Âgés) cohort followed for three years noninstitutionalized subjects aged ≥ 65 years without major neurocognitive impairment at inclusion. At each visit, an orthostatic systolic BP (SBP) ratio was calculated using the formula (sitting SBP/standing SBP) x 100. An orthostatic diastolic BP ratio was computed using the same method. Subjects with a SBP ratio > 100% had sitting SBP > standing SBP. We assessed the visit‐to‐visit BP postural changes variability according to several indicators: standard deviation, coefficient of variation (CV), variation independent of mean, residual standard deviation, average real variability, and successive variation. Cognitive performances were evaluated using the Mini‐Mental State Examination. Linear mixed models were used for the analyses. Result: We included 2, 974 subjects (mean age 78 years, women 56%). After adjustment for age, sex, education, baseline body mass index, smoking, alcohol intake, atrial fibrillation, congestive heart failure, transient ischemic attack or stroke, coronary artery disease, type 2 diabetes, dyslipidemia, seated SBP/DBP and antihypertensive treatment, greater visit‐to‐visit systolic BP postural changes variability was significantly associated with CD over time (adjusted β [95% CI] = ‐0.17 [‐0.29; ‐0.06], p = 0.004 for CV). Similar results were found for visit‐to‐visit diastolic BP postural changes variability (adjusted β [95% CI] = ‐0.14 [‐0.25; ‐0.03], p = 0.017 for CV). Conclusion: Greater visit‐to‐visit BP postural changes variability was associated with CD. Further studies are needed to assess whether controlling orthostatic BP instability over time could be a promising interventional target to preserve cognition among older adults.